Efektivitas Terapi Bermain Kolase Dan Plastisin Terhadap Perkembangan Motorik Halus Anak 4-5 Tahun Di Tk Zainul Hasan - Felda Amalia; Nafolion Nur Rahmat; Roisah Roisah (Pusat riset dan Inovasi Nasional, 2023)
Fine motor development is a movement that only involves small muscles in the body, such as skills in using fingers and wrist movements. Delays in fine motor development are caused by the lack of opportunities for children to play, the stimulation that children receive is good by parents. This study aims to determine the effectiveness of playing collage and plasticine therapy on fine motor development in children 4-5 years old at Zainul Hasan Genggong Kindergarten, ProbolinggoThis type of research is pre-experimental with a two group pretest-posttest research design. The population was 46 respondents who met the inclusion requirements of the study were selected using a total sampling technique. Children's fine motor development was measured using an observation sheet, and information was gathered using editing, coding, scoring, and tabulating procedures. In both groups, the data were evaluated using the Wilcoxon test hypothesis.The results showed that the value of ρ Value α = 0.000 in the collage playing group and the value of ρ Value α = 0000 in the plasticine playing group. The significant level of ρ Value < α 0.05, it is stated that both therapies are effective in developing children's fine motor development. However, judging by the results of the observation, the post-test value of playing plasticine therapy was more with the results of the BSB category being 20 children. Due to the age characteristics in group 2, there were more 4 years of age at that age, children's fine motor development was more rapid.Collage and plasticine games are a series of therapies to develop fine motor development in children. For further researchers, it is recommended to add variety of images in collage play therapy, to approach children more when given play therapy.